Retinal arterial macroaneurysm in a patient with arterial hypertension: Makroanevrizma retinalne arterije pri bolniku z arterijsko hipertenzijo - Masten, Matejka; Hudovernik, Mojca; Pahor, Dušica (Acta Medico-Biotechnica, 2021)
Purpose: To present a case of retinal arterial macroaneurysm in a 48–year–old male patient with systemic arterial hypertension.Case report: A 48–year–old male was admitted to our department because of progressive deterioration of visual acuity in his right eye. He reported diplopia and blurred central field vision. The patient was treated for systemic arterial hypertension and had no other known medical problems. Medical treatment, examination results, and therapy were presented in this case report.Conclusions: In the treatment of patients with retinal arterial macroaneurysm a holistic approach is important. In an attempt to optimize the final outcome of the patient's treatment, both the ocular symptoms and systemic risk factors should be treated. Therapeutic interventions for eyes with retinal arterial macroaneurysm include laser photocoagulation, pneumatic displacement of haemorrhage, vitreoretinal surgical techniques, the use of neodymium–doped yttrium aluminium garnet or argon laser, and intravitreal injections of anti–vascular endothelial growth factor drugs. Their precise roles should be evaluated in further studies.
Keywords: macroaneurysm; retinal haemorrhage; macular oedema; arterial hypertension